Parents' Strategies in Educating the Young Children to Memorize the Qur'an - Fairuzillah, Muhammad Naufal; Ilmiatun, Nelis Jamilah; Dirgantara, Yudi; Chaudhary, Muhammad Zafar Iqbal; Suharti, Suharti (UPI Kampus Cibiru, 2025)
The public interest of Muslim parents in educating their children to memorize the Qur’an seems to be highly large. Educating young children to become Hafiz-ul-Qur’an requires strategies that can support them to truly become Qur'anic memorizers. The aim of this research is to explore the parents’ strategies in educating their young children to become memorizers of the Qur'an. This is a qualitative study which used grounded theory analysis. There were four parents who involved in this study, those parents have been educating their young children to memorize the Qur’an in different backgrounds and domiciles in Indonesia. The conclusion of this study is that there are four strategies parents use in educating their children to memorize the Qur'an. Their strategies in educating the young children to memorize the Qur’an are trying to understand the characteristics of their children, applying habituation toward Al-Qur’an, motivating and giving them rewards, showing good example, consistency and discipline. The implication of this study is to examine in greater depth the strategies parents use in educating their children to become memorizers of the Qur'an. This research explores in depth how the parents’ strategies in educating their young children to memorize the Qur’an.